2022
DOI: 10.3389/fendo.2022.992883
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroidal feedforward and feedback network regulating thyroid hormone synthesis and secretion

Abstract: Thyroid hormones (THs), including T4 and T3, are produced and released by the thyroid gland under the stimulation of thyroid-stimulating hormone (TSH). The homeostasis of THs is regulated via the coordination of the hypothalamic-pituitarythyroid axis, plasma binding proteins, and local metabolism in tissues. TH synthesis and secretion in the thyrocytes-containing thyroid follicles are exquisitely regulated by an elaborate molecular network comprising enzymes, transporters, signal transduction machineries, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 282 publications
(369 reference statements)
0
15
0
Order By: Relevance
“…The thyrotropin-releasing hormone (TRH) produced by neurons in the hypothalamic paraventricular nucleus (PVN) stimulates the synthesis and release of the thyroid-stimulating hormone (TSH) in the anterior pituitary. TSH then stimulates the production and release of T4 and T3 by the thyroid follicles ( 6 ). Negative feedback from T4 and T3 occurs through the inhibition of both TRH and TSH, which keeps the circulating free TH levels close to the setpoints in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…The thyrotropin-releasing hormone (TRH) produced by neurons in the hypothalamic paraventricular nucleus (PVN) stimulates the synthesis and release of the thyroid-stimulating hormone (TSH) in the anterior pituitary. TSH then stimulates the production and release of T4 and T3 by the thyroid follicles ( 6 ). Negative feedback from T4 and T3 occurs through the inhibition of both TRH and TSH, which keeps the circulating free TH levels close to the setpoints in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is known from other studies that oxidative metabolism in thyrocytes is enhanced by the action of TSH [36]. In addition, ATP is required to enhance synthetic thyroid function by TSH [23]. Although we were not able to measure rat TSH serum concentration it should be noted that Yi et al observed similar morphological changes in the thyroid gland of rats under the influence of PTU, which were attributed to an increase in TSH secretion due to reduced biosynthetic function of the thyroid gland [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ATP is the source for the synthesis of cAMP, an important second messenger in the cells [22]. Numerous studies have shown that one of the links in the signaling pathway leading from the TSH receptor to the synthesis of thyroid hormones is cAMP, which is activated by the Gα s subunit [23]. Moreover, it has been shown that curcumin may increase cAMP levels in skeletal muscle [24] and pancreatic beta-cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…The content of this section is based on Hernández et al, 2020;Nielsen et al, 2012;Jing & Zhang, 2022. The thyroid gland is located within the visceral compartment of the neck (along with the trachea, oesophagus and pharynx). It consists of two lobes, right and left, on each side of the trachea, joined together in humans by an intermediate structure called the isthmus.…”
Section: Thyroid Anatomy and Physiologymentioning
confidence: 99%